Optofluidics: the interaction between light and flowing liquids in integrated devices - Zhu Jiaomeng (Institue of Optics and Electronics, Chinese Academy of Sciences, 2019)
Optofluidics is a rising technology that combines microfluidics and optics. Its goal is to manipulate light and flowing liquids on the micro/nanoscale and exploiting their interaction in optofluidic chips. The fluid flow in the on-chip devices is reconfigurable, non-uniform and usually transports substances being analyzed, offering a new idea in the accurate manipulation of lights and biochemical samples. In this paper, we summarized the light modulation in heterogeneous media by unique fluid dynamic properties such as molecular diffusion, heat conduction, centrifugation effect, light-matter interaction and others. By understanding the novel phenomena due to the interaction of light and flowing liquids, quantities of tunable and reconfigurable optofluidic devices such as waveguides, lenses, and lasers are introduced. Those novel applications bring us firm conviction that optofluidics would provide better solutions to high-efficient and high-quality lab-on-chip systems in terms of biochemical analysis and environment monitoring.